Preparation for certain and uncertain future outcomes in young children and three species of monkey. Issue 2 (1st August 2019) - Suddendorf, Thomas; Watson, Kate; Bogaart, Maddison; Redshaw, Jonathan
Abstract: This study examined 3‐year old children and monkeys' capacities to prepare for immediate future events. In Study 1, children were presented with several tube apparatuses with two exits. When targets were certain to emerge from both, children tended to prepare to catch them by covering each exit. When it was uncertain where targets would emerge, however, they tended to prepare for only one possibility. These results substantiate the claim that simultaneous preparation for mutually exclusive possibilities develops relatively late. Study 2 found no evidence for such a capacity in monkeys ( Ateles geoffroyi, Cebus apella, Papio hamadryas ) given the same tasks.